The conformational behaviour of naproxen and flurbiprofen in solution by NMR spectroscopy. (30th September 2015) - Di Pietro, Maria Enrica; Aroulanda, Christie; Celebre, Giorgio; Merlet, Denis; De Luca, Giuseppina
Abstract : The conformational equilibrium of common anti-inflammatory drugs has been studied experimentally in solution by NMR in weakly ordered PBLG phases. Abstract : Naproxen and flurbiprofen are among the most popular and widely used drugs for treating pain and inflammation and new different therapeutic uses are still being proposed. Their pharmacological activity comes from the specific binding to target proteins and is evidently driven by the spatial arrangement they adopt at the active sites. A detailed conformational elucidation analysis in solution able to probe equilibria between more possible conformers is then crucial for understanding and rationalizing their biological role and possibly for designing improved analogues. Here we combine NMR data obtained in weakly ordered media and suitable theoretical models to look for the energetically admissible conformers of these two anti-inflammatory drugs in a liquid medium. This approach leads to rather complex probability distributions characterized for both molecules by an equilibrium of different global and local minimum energy structures.